Comanthera gandarela, a critically endangered new species from the ferruginous campos rupestres (Cangas) of Serra do Gandarela, Minas Gerais, Brazil (Eriocaulaceae) - Echternacht, Livia; Souto, Danielle; Silva, Luzimar; de Lima, Thales; Ramos, Renato (Phytotaxa, 2025)
The present work describes and illustrates Comanthera gandarela (Eriocaulaceae), a new and narrowly endemic species. It is unique within the genus for being restricted to ferruginous Campos Rupestres (Cangas) in the Serra do Gandarela, within the Quadrilátero Aquífero-Ferrífero, Minas Gerais, Brazil. The species is distinguished from C. nivea, the morphologically and geographically closest species, by its semi-terete leaves, spathes surpassing the leaves, convex and semi-spherical receptacle and flower disc in mature inflorescences, with involucral bracts reflexed, elongated stem in mature individuals, and canescent leaves. In addition to external morphology, we present anatomical sections of the leaves and scapes, as well as Scanning Electron Microscopy images of the leaf epidermis, scapes, and seeds. The species’ habitat, distribution, population, conservation status, and threats are also discussed. Comanthera gandarela is preliminarily assessed as Critically Endangered under IUCN criteria B1ab(i, ii, iii, iv), facing intense habitat destruction pressure.